Bailey & Love's short practice of surgery - Bailey, Hamilton , 1894-1961; Bulstrode, C. J. K. [ (Christopher J. K.)]; Love, R. J. McNeill [ (Robert John McNeill)] , 1891-1974; O'Connell, P. Ronan; Williams, Norman S. , 1947- (CRC Press, 2013)
One of the world's pre-eminent medical textbooks, beloved by generations of surgeons both in the UK and in numerous countries overseas, with lifetime sales in excess of one million copies.